183k views
3 votes
If f(x) = 3 -3 and g(x) = 3x² + x - 6, find (f+ 9)(x).​

If f(x) = 3 -3 and g(x) = 3x² + x - 6, find (f+ 9)(x).​-example-1
User Houssam
by
5.3k points

1 Answer

1 vote

Answer:


\displaystyle B. \ 3x^2 + (3)/(2)x - 9

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Terms/Coefficients
  • Functions

Explanation:

Step 1: Define

Identify


\displaystyle f(x) = (x)/(2) - 3


\displaystyle g(x) = 3x^2 + x - 6

Step 2: Find

  1. Substitute in functions:
    \displaystyle (f + g)(x) = (x)/(2) - 3 + 3x^2 + x - 6
  2. Combine like terms:
    \displaystyle (f + g)(x) = 3x^2 + (3)/(2)x - 9
User Avery
by
5.2k points